Strategi Berbasis Bimbingan Konseling dalam Mengatasi Keterlibatan Santri Bermain Judi Online - Putra, Ahmad (Program Studi Bimbingan dan Konseling Islam (BKI) Fakultas Ushuluddin, Adab dan Dakwah (FUAD) Institut Agama Islam Negeri (IAIN), 2024)
Online gambling is currently a serious scourge that is affecting various groups of people. The impact is truly worrying, so this problem cannot be taken lightly, especially if efforts are not made to overcome things that could have increasingly severe impacts. One group that is quite at risk of becoming victims of online gambling cases are students who are still considered students, which should be the obligation of all related parties to protect and save the generation from being involved in this negative trend. This is the reason why guidance and counseling teachers provide reinforcement and strategies through which students can be saved. The author's approach in this research is a qualitative approach with descriptive methods. The author's research was conducted at the Minangkabau Village Islamic Boarding School, Padang City, West Sumatra Province. In this research, the subjects were guidance and counseling teachers and students who received material on various matters relating to anticipation and efforts to save students from online gambling addiction. The results of the research show that, first, the guidance and counseling teacher prepared material regarding the dangers of online gambling for students and presented it at the 2024 Matsama (Marasa Taaruf for Madrasah Students) event, second, the guidance and counseling teacher opened a counseling service for students who are addicted to online gambling or who want to go deeper. knowing the negative impacts that result, third, BK teachers build synergy with Islamic boarding school leaders by again trying to strengthen the rules that apply in Islamic boarding schools by prohibiting bringing cell phones to school and in dormitories for all students, fourth, BK teachers hold group guidance activities with the topic